Thermal conductivity and properties of cyanate Ester/nanodiamond composites - KAHRAMAN, MEMET VEZİR (WILEY, 2014)
The aim of this study was to improve thermal conductivity, thermal stability, and mechanical properties of bisphenol A dicyanate ester with the addition of nanodiamond. Cyanate ester/nanodiamond composites containing various ratios of nanodiamond were prepared. Thermal stability and thermal conductivity of the samples were evaluated by thermogravimetric analysis, differential scanning calorimetry, and laser flash method, respectively. The samples were characterized with the analysis such as gel content, water absorption capacity, and stress-strain test. Hydrophobicity of the samples was determined by contact angle measurements. Moreover, the surface morphology of the samples was investigated by a scanning electron microscopy. The obtained results prove that the cyanate ester/nanodiamond composites have good thermal and mechanical properties and can be used in many applications such as the electronic devices, materials engineering, and other emergent. Copyright (C) 2014 John Wiley & Sons, Ltd.
Keywords: cyanate esters; nanodiamond; thermal conductivity; nanocomposites; scanning electron microscopy; ESTER; NANODIAMOND